2013
DOI: 10.1093/cvr/cvt112
|View full text |Cite
|
Sign up to set email alerts
|

Factor-Xa-induced mitogenesis and migration require sphingosine kinase activity and S1P formation in human vascular smooth muscle cells

Abstract: These data suggest that FXa induces SPHK1 expression and increases S1P formation independent of thrombin and that this involves the activation of Rho A and PKC signalling. In addition to its key function in coagulation, this direct effect of FXa on human SMC may increase cell proliferation and migration at sites of vessel injury and thereby contribute to the progression of vascular lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 43 publications
2
31
0
Order By: Relevance
“…S1P has also been well proven to impact cell migration in VSMCs [41]. Based on our observation, Sphk1 expression and S1P synthesis were markedly increased by CRF.…”
Section: Discussionsupporting
confidence: 65%
“…S1P has also been well proven to impact cell migration in VSMCs [41]. Based on our observation, Sphk1 expression and S1P synthesis were markedly increased by CRF.…”
Section: Discussionsupporting
confidence: 65%
“…This study is, to the best of our knowledge, the first to clarify the role of the DJ-1 protein in SPL-mediated VSMC function. Furthermore, our results suggest that the control of the S1P production and secretion on VSMCs is helpful for the modulation of vascular disorders via the diminution of autocrine S1P [6].…”
mentioning
confidence: 78%
“…Recent work from our laboratory has shown that FXa regulates transcription of SPHK1 and elevates S1P biosynthesis in human vascular smooth muscle cells (Fig. 1A, 1B) [46]. This stimulatory effect, observed in cultured cells, was seen at FXa concentrations (3 to 30 nM) which have been shown to occur during thrombus formation ex vivo [8].…”
Section: Clotting Factor-induced Sphk1 Expression and S1p Production mentioning
confidence: 89%
“…Overlay (yellow) indicates a spatial association of both proteins in human atherosclerotic plaques. Modified after Böhm et al [46]. …”
Section: Clotting Factor-induced Sphk1 Expression and S1p Production mentioning
confidence: 99%